HEPATIC ISCHEMIA REPERFUSION INJURY IN SEPSIS: BASIS PATHOGENIC MECHANISMS - Suryadarma, I Gusti Agung (journal of internal medicine; Vol. 8, No. 2 Mei 2007)
Hepatic ischemia reperfusion injury is a complex patho-physiology with a number contributing factors. Ischemia insult can lead to sublethal cell injury, which is aggravated by the formation of reactive oxygen from various intracellular sources during reperfusion. In addition, formation of proinflammatory mediators and the recruitment and activation of macrophages, neutrophil and lymphocyte can further enhance the injury. Microcirculatory disturbances lead to underperfused areas in the liver and may cause ischemic injury. Hepatic IR injury involves interaction between different cell types and a variety of cellular and molecular mechanisms including kupffer cells activation, formation of ROS, release of cytokines and chemokines, neutrophil recruitment, mitochondrial permeability transition and pH paradox. There are two distinct phase of liver injury after warm ischemic reperfusion, such as early phases and followed by late phases. Clinical presentation of hepatic ischemic reperfusion injury in sepsis, including sepsis-associated cholestasis, hepatitis ischemic, cholangitis lenta and progressive sclerosing cholangitis
Keywords: Hepatic ischemia